2016
DOI: 10.1089/end.2015.0534
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Disease and Chronic Obstructive Pulmonary Disease Increase Risk of Complications with Robotic Partial Nephrectomy

Abstract: Bauman, Tyler M.; Potretzke, Aaron M.; Vetter, Joel M.; Bhayani, Sam B.; and Sherburne Figenshau, Robert, ,"Cerebrovascular disease and chronic obstructive pulmonary disease increase risk of complications with robotic partial nephrectomy." Journal of Endourology.30,3. 293-299. (2016

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…By avoiding a large open incision, we hypothesized that the robot‐assisted approach may decrease morbidity in obese patients. Because obesity‐related comorbidities are prevalent in the obese population and may have a confounding effect on peri‐operative outcomes, we chose to study obese patients who were otherwise healthy, as defined by a low comorbidity burden (CCI ≤1) and the presence of two functioning kidneys . We found that the robot‐assisted approach offers clear advantages over the open approach in terms of shorter operating time, fewer postoperative complications and shorter LOS.…”
Section: Discussionmentioning
confidence: 99%
“…By avoiding a large open incision, we hypothesized that the robot‐assisted approach may decrease morbidity in obese patients. Because obesity‐related comorbidities are prevalent in the obese population and may have a confounding effect on peri‐operative outcomes, we chose to study obese patients who were otherwise healthy, as defined by a low comorbidity burden (CCI ≤1) and the presence of two functioning kidneys . We found that the robot‐assisted approach offers clear advantages over the open approach in terms of shorter operating time, fewer postoperative complications and shorter LOS.…”
Section: Discussionmentioning
confidence: 99%
“…The team from Fox Chase reported a strong correlation between tumour complexity and complications when they published their initial study of the RENAL score [18], but other groups failed to identify a similar link [21,22]. Some authors reported an association between patients' comorbidities and complications after RPN [23,24], but this relationship was not confirmed by others [3].…”
Section: Discussionmentioning
confidence: 99%
“…Moskowitz et al[28] demonstrated 11.3% of patients experiencing postoperative complication and not associated with surgeon experience. Additionally, a study of 641 consecutive RAPNs in the Washington University demonstrated that cerebrovascular disease was a predictor of perioperative complication [29]. The oncological safety is of the paramount importance in cancer surgery [30].…”
Section: Discussionmentioning
confidence: 99%